Expanding the phenotypic spectrum of GABRG2 variants: a recurrent GABRG2 missense variant associated with a severe phenotype. (3rd April 2017) - Zou, Fanggeng; McWalter, Kirsty; Schmidt, Lindsay; Decker, Amy; Picker, Jonathan D.; Lincoln, Sharyn; Sweetser, David A.; Briere, Lauren C.; Harini, Chellamani; ,; Marsh, Eric; Medne, Livija; et al.
Abstract: Pathogenic missense and truncating variants in the GABRG2 gene cause a spectrum of epilepsies, from Dravet syndrome to milder simple febrile seizures. In most cases, pathogenic missense variants in the GABRG2 gene segregate with a febrile seizure phenotype. In this case series, we report a recurrent, de novo missense variant (c0.316 G > A; p.A106T) in the GABRG2 gene that was identified in five unrelated individuals. These patients were described to have a more severe phenotype than previously reported for GABRG2 missense variants. Common features include variable early-onset seizures, significant motor and speech delays, intellectual disability, hypotonia, movement disorder, dysmorphic features and vision/ocular issues. Our report further explores a recurrent pathogenic missense variant within the GABRG2 variant family and broadens the spectrum of associated phenotypes for GABRG2 -associated disorders.